2020
DOI: 10.1109/jsait.2020.2986752
|View full text |Cite
|
Sign up to set email alerts
|

Deepcode: Feedback Codes via Deep Learning

Abstract: The design of codes for communicating reliably over a statistically well defined channel is an important endeavor involving deep mathematical research and wide-ranging practical applications. In this work, we present the first family of codes obtained via deep learning, which significantly beats state-of-the-art codes designed over several decades of research. The communication channel under consideration is the Gaussian noise channel with feedback, whose study was initiated by Shannon; feedback is known theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
177
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(180 citation statements)
references
References 44 publications
2
177
1
Order By: Relevance
“…Although we have considered Deepcode as channel code for our experiments, we found that the proposed scheme cannot be easily employed for the transmission of images in large blocklengths. The results presented in [30] consider transmission of a message of 50 bits at rate 1/3 on the forward channel SNR range -2dB -1dB. In this range (-2dB -1dB), indeed Deepcode outperforms other channel codes; however, we found that none of our source codes could achieve a non-trivial PSNR value that improves upon the quality obtained when averaging all pixels with their average values (lower bound considered in case of failed transmissions).…”
Section: A Deepjscc-f With Two Layers (L = 2)mentioning
confidence: 83%
See 3 more Smart Citations
“…Although we have considered Deepcode as channel code for our experiments, we found that the proposed scheme cannot be easily employed for the transmission of images in large blocklengths. The results presented in [30] consider transmission of a message of 50 bits at rate 1/3 on the forward channel SNR range -2dB -1dB. In this range (-2dB -1dB), indeed Deepcode outperforms other channel codes; however, we found that none of our source codes could achieve a non-trivial PSNR value that improves upon the quality obtained when averaging all pixels with their average values (lower bound considered in case of failed transmissions).…”
Section: A Deepjscc-f With Two Layers (L = 2)mentioning
confidence: 83%
“…While it is shown in [30] that the proposed DNN-based feedback channel code provides some level of robustness against noise in the feedback channel, to the best of our knowledge, this is the first practical JSCC scheme that is robust to feedback channel noise. Figure 12 shows the performance for different feedback channel SNRs (0 dB, 10 dB, 20 dB, and noiseless) and the single layer model (no feedback).…”
Section: Noisy Feedbackmentioning
confidence: 96%
See 2 more Smart Citations
“…Most of the prior studies are aimed at learning and/or improving the performance of decoding algorithms through the use of a neural network. There are only a few papers that aim to learn an encoder, which is more difficult than learning a decoder due to the difficulties of training the lower layers in deep networks [13], [14], [15]. We specifically design a channel code for the challenging one-bit quantized AWGN channels via an autoencoder to obtain reliable communication at the Shannon rate.…”
Section: A Related Work and Motivationsmentioning
confidence: 99%